The Role of Effective Leadership in Application of E-Human Resources Management System Applied research at Baghdad International Airport - Mohammed Ali, Alia Jawad; Weli, Ameera Shukur (Journal of Economics and Administrative Sciences, 2020)
The research acquires its importance by motivating the behavioural side of the employees to apply modern technology in the work, because of its great importance in increasing the efficiency of employees’ performance and excellence. The research was based on two main hypotheses to show the relationship and impact between the variables through the adoption of a questionnaire to collect data and information related to the research, which consisted of (50) people from administrators working at different levels, based on personal interviews and field visits to collect research data. The data collection process was subjected to statistical analysis using the statistical program (SPSS) (Statistical package for social science) to reach a set of results which showed a positive correlation between the variable of effective leadership and the variable of (E-HRM). The research was conducted at (Baghdad International Airport). It’s included questionnaire distribution on the research sample, collecting the questionnaire, field visits and analysis of the results. The research also concluded that effective leaders should have a role in change the behaviour of employees and improving their level of performance, and train them to use technology at work. The research also presented several suggestions, including the importance of training employees with the adoption of material and moral incentives for those who are distinguished in the application and use of modern technology, as well as providing all the tools physical requirements for the application and success of the (E-HRM) and processed.Paper type Field research